Assessing UiTM TESL students’ knowledge of vocabulary / Leele Susana Jamian, Gurnam Kaur Sidhu and Muzaireen Muzafar - Jamian, Leele Susana; Gurnam Kaur Sidhu; Muzafar, Muzaireen (ACRULeT, Faculty of Education & UiTM Press, 2008)
Learning the vocabulary of a language is vital in the process of acquiring the language because it serves several functions which assist learners to be good at the language, even though learning can be complicated and burdening for learners (Jiang, 2004; Cobb & Horst, 2004). The aim of the study was to investigate the English vocabulary levels of the TESL mainstream students in Universiti Teknologi MARA (UiTM). This research study also examined the differences in vocabulary levels between the male and female students. The study involved 90 respondents that were enrolled in the TESL programme at the Faculty of Education in UiTM, Shah Alam. The findings revealed that most of the UiTM TESL students scored an average of 15 correct answers in the 2,000 word-level, 12 for the 3,000 word-level, 8 for the 5,000 word-level, 10 for the University Word Level and 6 for the 10,000 word-level. The study also revealed that even though the students were highly engaged with listening, reading, speaking and writing activities, these involvements did not correlate with the mastery of vocabulary knowledge.